2016
DOI: 10.3389/fonc.2016.00144
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia on the Expression of Hepatoma Upregulated Protein in Prostate Cancer Cells

Abstract: Hepatoma upregulated protein (HURP) is a multifunctional protein with clinical promise. This protein has been demonstrated to be a predictive marker for the outcome in high-risk prostate cancer (PCa) patients, besides being a resistance factor in PCa. Although changes in oxygen tension (pO2) are associated with PCa aggressiveness, the role of hypoxia in the regulation of tumor progression genes such as HURP has not yet been described. We hypothesized that pO2 alteration is involved in the regulation of HURP ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 57 publications
0
16
0
Order By: Relevance
“…DLGAP5, a microtubule-associated protein, is phosphorylated by Aurora kinase A (AURKA) (43). In addition, DLGAP5 upregulation is associated with poor prognosis of patients with colorectal cancer (44), lung cancer (10), bladder cancer (11) and prostate cancer (12), indicating that DLGAP5 plays an important role in cancer prognosis. Branchi et al (44) reported that DLGAP5 was associated with the nodal status, and high DLGAP5 expression levels were associated with a less favorable overall survival rate in distinct molecular colorectal cancer subtypes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…DLGAP5, a microtubule-associated protein, is phosphorylated by Aurora kinase A (AURKA) (43). In addition, DLGAP5 upregulation is associated with poor prognosis of patients with colorectal cancer (44), lung cancer (10), bladder cancer (11) and prostate cancer (12), indicating that DLGAP5 plays an important role in cancer prognosis. Branchi et al (44) reported that DLGAP5 was associated with the nodal status, and high DLGAP5 expression levels were associated with a less favorable overall survival rate in distinct molecular colorectal cancer subtypes.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, targeting mitosis-associated genes, including DLGAP5, TPX2 and RAN, has been reported to induce apoptosis of the BRG1 mutant NSCLC cells, both in vitro and in vivo (47). Espinoza et al (12) demonstrated that DLGAP5 was a predictive biomarker for the prognosis of high-risk prostate cancer in addition to functioning as a resistance factor. Furthermore, hypoxia-inducible factor 1-alpha (HIF-1α) binding sites were revealed on the promoter of DLGAP5, indicating that hypoxia plays a modulatory role on DLGAP5 expression (11).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, apart from promoting cancer cells proliferation, what other functions does it have? Indeed, based on bioinformatics analysis, it has been found that DLGAP5 involved in the occurrence, development and prognosis of malignant tumors [18,24], and may serve as potential molecular biomarkers for a set of carcinomas, including glioblastoma [24], prostate cancer [16,17,25]. Interestingly, DLGAP5 protein has been found to be one of top ten oxygen-sensitive proteins in prostate cancer [16,26], and is proposed as an independent prognostic biomarker in this tumor [16].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, DLGAP5 protein has been found to be one of top ten oxygen-sensitive proteins in prostate cancer [16,26], and is proposed as an independent prognostic biomarker in this tumor [16]. By using the published date, it has been found that several putative HIF binding sites located at promoter region of DLGAP5, most of which are highly methylated region [16,25]. In addition, the inhibitory effect of DLGAP5 knockout on prostate cancer is related to androgen receptor [17].…”
Section: Introductionmentioning
confidence: 99%